Arthropathy in Patients with Moderate Hemophilia A: A Systematic Review of the Literature - Di Minno, Matteo Nicola Dario; Ambrosino, Pasquale; Franchini, Massimo; Coppola, Antonio; Di Minno, Giovanni (Seminars in Thrombosis and Hemostasis, 2013)
Chronic arthropathy is a major complication in severe hemophilia A (Factor [F] VIII < 1%). Almost all adults with severe hemophilia, who have not received prophylaxis with FVIII since their early childhood, suffer from chronic arthropathy. Patients with moderate hemophilia (FVIII activity 1–5%) usually experience fewer joint bleeds than those with severe hemophilia and are thought to rarely develop a significant degree of chronic arthropathy. However, some patients with moderate hemophilia behave like those with the severe form of the disorder, reporting several joint bleeds per year and significant joint impairment. Currently, only little data are available about the prevalence of arthropathy, the degree of quality of life impairment, and the need for orthopedic care/aids in patients with moderate hemophilia. In this systematic review of literature, the prevalence of overt arthropathy ranges between 15 and 77% in patients with moderate hemophilia and prophylactic replacement treatment is prescribed in approximately 30% of these patients, usually after diagnosis of clinically overt arthropathy. Moreover, because of the lack of imaging studies (magnetic resonance and/or ultrasound), the prevalence of subclinical arthropathy cannot be determined. These data confirm that severity of hemophilia should not be defined only according to FVIII levels and that a relevant proportion of patients with nonsevere hemophilia might benefit from a “tailored early prophylaxis.”
Keywords: moderate hemophilia; arthropathy; prophylaxis